2014
DOI: 10.1080/17565529.2014.951019
|View full text |Cite
|
Sign up to set email alerts
|

Future sea changes: Indigenous women's preferences for adaptation to climate change on South Goulburn Island, Northern Territory (Australia)

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…In addition to contributing to improved health through dietary intake, the socio‐cultural contribution and opportunity for physical activity that traditional foods provide is important to recognise 21,32,33 . The impact that climate change, changes in the natural environment and development policies regarding land and sea use may have on traditional food use and thus health and wellbeing is critical to understand 12,32,34 . Although not designed to collect information on environmental and other impacts on traditional food, this study suggests that introduced animals are affecting the availability of small animal and plant foods, at least in the Top End of the NT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to contributing to improved health through dietary intake, the socio‐cultural contribution and opportunity for physical activity that traditional foods provide is important to recognise 21,32,33 . The impact that climate change, changes in the natural environment and development policies regarding land and sea use may have on traditional food use and thus health and wellbeing is critical to understand 12,32,34 . Although not designed to collect information on environmental and other impacts on traditional food, this study suggests that introduced animals are affecting the availability of small animal and plant foods, at least in the Top End of the NT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the use of traditional foods may be gaining interest nationally and internationally, and in addition to being good for human and environmental health, could provide economic and employment opportunities for Aboriginal and Torres Strait Islander Australians 37 . There is a developing interest in sustainability of traditional foods in environmental protection efforts, 12 such as working with Aboriginal people to develop adaption strategies to mitigate the impact of climate change on the environment and traditional food supply 32,34 . Similarly, traditional food data are used internationally to maintain and improve availability and access to traditional foods as a result of global warming and environmental insults, such as contamination 17,18,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was part of a larger project that investigated Indigenous women's understanding of climate change in relation to its potential impacts on customary marine harvesting and their views on sea-based aquaculture as a potential adaptation strategy (Petheram et al, 2013(Petheram et al, , 2014. This paper focuses on the results relating to preferences for aquaculture development.…”
Section: Conceptual Framework and Data Collection And Analysismentioning
confidence: 99%
“…Most published studies that document adaptation efforts in the Arctic tend to focus on communities that are advanced or imminently threatened. It is also notable that many of these documented efforts lack traditional knowledge inclusion in a meaningful way, as similarly found in other adaptation efforts outside of the Arctic (Boillat and Berkes 2013;Petheram et al 2014;Carmichael et al 2017;Ali et al 2019;Mugambiwa and Rukema 2019). We posit that focusing on climate-related issues that are emergentnot just those that are long-standing or acute-provides a critical way to proactively address climate impacts before they become too extreme, unwieldy, or costly to sufficiently address.…”
Section: Introductionmentioning
confidence: 84%